Pré-natal: perfil de mulheres residentes no município de Santarém - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Prenatal care is one of the most important components for the care and monitoring of women's health during the gestational period, making it essential for the protection and prevention of adverse events for maternal and neonatal health. In Brazil, this monitoring is carried out through the Unified Health System (SUS), through the Primary Health Care (PHC) teams. And to guarantee comprehensive care for this public, the Ministry of Health created in 1984 the Comprehensive Assistance Program for Women's Health (PAISM), ensuring that assistance is provided to this woman. In this way, this study will present data referring to the analysis of prenatal care in women residing in the municipality of Santarém between the years 2011 to 2020. It is an epidemiological study, with a quantitative, descriptive, and exploratory approach, in which pre-existing data available for public consultation was used. Data collection was carried out through the Information Department of the Unified Health System (DATASUS), on December 15, 2022, through the Live Births Information System (SINASC). Data were collected on the website and later organized into spreadsheets in the Microsoft Excel program and then transformed into tables for data analysis. The following variables were used: maternal age, marital status, level of education, duration of pregnancy, prenatal consultations, type of delivery, type of pregnancy, place of occurrence, sex, color/race. A total of 66,115 live births were identified in the city of Santarém between 2011 and 2020. Of these women who had children, about 99.9% were of childbearing age and were followed up in the city's health care network. As for the sociodemographic profile, they were aged between 15 and 29 years; with marital status of consensual union, followed by single mothers; they had an education level of 8 to 11 years of schooling and declared themselves brown. With regard to the characterization of prenatal and childbirth care for women residing in the municipality of Santarém, it was found that most performed the number of consultations recommended by health agencies of six or more consultations; had a baby considered at term and for the type of pregnancy, regarding the number of conceptuses, single gestation prevailed, with a prevalence of births of male babies and the main route was vaginal delivery, and regarding the place of birth occurred mainly in a hospital environment, but this study also showed a very significant percentage of deliveries that took place at home, this occurrence can be explained by the difficulty of getting to hospitals in the city on time due to the place of residence. The results of the study can support discussions on access to health services in urban, rural, quilombola, indigenous and riverside territories and on the implementation of public policies aimed at this public, guaranteeing comprehensive care that reflects on the improvement of maternal and child health indicators.
Keywords: Mulheres; Gestantes; Cuidado Pré-Natal; CNPQ:: CIÊNCIAS DA SAÚDE